Community Awareness and Involvement Towards Ecotourism Activities in Ranau, Sabah - Andy R. Mojiol (UCTS Publisher, 2018)
The question of whether the impact of having rural communities nearby an ecotourism area being positive or negative is one of the important issues in Ranau. Cooperation between villagers and park operator on the growth of tourists’ arrival is crucial and must be addressed. The aim of this study is to identify the local communities’ perception at Kampung Poring and Kampung Monggis, Ranau by mean if the ecotourism activities can uplift their economic, social, physical and general impression that they experienced. In addition, the involvements of local communities in ecotourism activities in their villages were also studied. A survey and face to face interview were carried out on a sample of 146 villagers from both study areas. Data analysis using frequency, mean scores and Pearson Correlation (2-sided) was conducted. From the result, positive perception has been perceived by the villagers as a result of the improvement of ecotourism activities such as increase in employment opportunities, infrastructure facilities have been upgraded, additional revenue sources for state governments and villagers as well as increase in Small and Medium Industries (SMIs). However, the perception and level of involvement of both villages is still at the moderate level, where many other issues still need to be improved in the future such as communication skills and accommodations. In conclusion, this matter should not be taken lightly so as not to occur dissatisfaction among villagers. Therefore, the park management party should be sensitive to this situation in order to maintain the welfare of the villagers and at the same time giving satisfaction to the tourists who enjoy ecotourism activities there.